Current advances in the development of microRNA-integrated tissue engineering strategies: a cornerstone of regenerative medicine - Castañón-Cortés, Luis Germán; Bravo-Vázquez, Luis Alberto; Santoyo-Valencia, Grecia; Medina-Feria, Sara; Sahare, Padmavati; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Bioengineering and Biotechnology, 2024)
Regenerative medicine is an innovative scientific field focused on repairing, replacing, or regenerating damaged tissues and organs to restore their normal functions. A central aspect of this research arena relies on the use of tissue-engineered scaffolds, which serve as structural supports that mimic the extracellular matrix, providing an environment that orchestrates cell growth and tissue formation. Remarkably, the therapeutic efficacy of these scaffolds can be improved by harnessing the properties of other molecules or compounds that have crucial roles in healing and regeneration pathways, such as phytochemicals, enzymes, transcription factors, and non-coding RNAs (ncRNAs). In particular, microRNAs (miRNAs) are a class of tiny (20-24 nt), highly conserved ncRNAs that play a critical role in the regulation of gene expression at the post-transcriptional level. Accordingly, miRNAs are involved in a myriad of biological processes, including cell differentiation, proliferation, and apoptosis, as well as tissue regeneration, angiogenesis, and osteogenesis. On this basis, over the past years, a number of research studies have demonstrated that miRNAs can be integrated into tissue-engineered scaffolds to create advanced therapeutic platforms that precisely modulate cellular behavior and offer a controlled and targeted release of miRNAs to optimize tissue repair and regeneration. Therefore, in this current review, we discuss the most recent advances in the development of miRNA-loaded tissue-engineered scaffolds and provide an overview of the future outlooks that should be aborded in this area of study in order to lay the groundwork for the clinical translation of these tissue engineering approaches.